DEVELOPMENT OF A TREATMENT SYSTEM FOR ANTIBIOTIC WASTEWATER - MOHAMMED, EMAD SOLIMAN MOHAMMED (2010)
Antibiotics are emerging contaminants in the aquatic environment because of their adverse effects on aquatic life and humans. The problem that may be created by the presence of antibiotics at low concentration in the environment is the development of antibiotic resistant bacteria. Antibiotic sources in the environment are antibiotic industry, human excretion and excretion form livestock. No work has been reported on complete treatment of antibiotic wastewater containing amoxicillin, ampicillin and cloxacillin. The overall objective of this work was development of an effective treatment system for antibiotic wastewater from an antibiotic industry producing these antibiotics. The work was conducted in three phases. In Phase I, four advanced oxidation processes (AOPs) (Fenton, photo-Fenton, UV/TiO2 and UV/ZnO) were applied for treatment of amoxicillin, ampicillin and cloxacillin antibiotics in aqueous solution. From a technical point of view, Fenton, photo-Fenton and UV/H2O2/TiO2 processes were able to degrade the antibiotics and improve biodegradability; however, UV/ZnO process did not improve biodegradability. Based on DOC removal, the photo-Fenton process exhibited the highest rate constant (0.029 min-1) followed by the Fenton (0.0144 min-1), UV/ZnO (0.00056 min-1) and UV/H2O2/TiO2 (0.0005 min-1). From an economic point of view, the photo-Fenton process appeared to be the most cost-effective compared to the other studied processes. In Phase II, the feasibility of using three combined AOP and sequencing batch reactor (SBR) (Fenton-SBR, photo-Fenton-SBR and UV/H2O2/TiO2-SBR) for complete treatment of an antibiotic wastewater from a local antibiotic industry producing amoxicillin, ampicillin and cloxacillin, was evaluated. Combined systems were operated for several months to study the effect of AOP and SBR operating conditions on the combined system performance. From a technical point of view, both combined Fenton-SBR and photo-Fenton-SBR systems achieved an overall efficiency of 89% for sCOD removal and the final effluent met the discharge standard. However, the combined UV/H2O2/TiO2-SBR system was not a feasible combined system for treatment of the antibiotic wastewater. From an economic point of view, the combined Fenton-SBR system appeared to be more costviii effective than the combined photo-Fenton-SBR system. The Monod kinetic model was fitted to the results of biodegradation of the Fenton-treated effluent by SBR under the best operating conditions with the kinetic constants kob 0.078 hr-1, YX/S 0.60 and Kd -0.0013 hr-1. The values of kob, YX/S and Kd for biodegradation of the photo- Fenton-treated effluent under the best operating conditions were similar to those of Fenton-treated effluent. In Phase III, artificial neural network (ANN) was applied for modelling, simulation and prediction of the Fenton process performance. ANN predicted results were very close to the experimental results with correlation coefficient of 0.997 and mean square error of 0.000376. The sensitivity analysis showed that all studied variables have strong effect on COD removal and H2O2/Fe2+ molar ratio is the most influential parameter. The study showed that neural network modelling could effectively predict and simulate the behaviour of the Fenton process. The study culminated in development of an effective treatment systems for antibiotic wastewater. From technical and economic point of view, combined Fenton-SBR system was the most effective for treatment of the antibiotic wastewater.